Clinicopathological differentiation between Pityrosporum folliculitis and acneiform eruption. Issue 11 (5th September 2019) - An, Min Kyun; Hong, Eun Hye; Cho, Eun Byul; Park, Eun Joo; Kim, Kwang Ho; Kim, Kwang Joong
Abstract: Distinguishing between Malassezia folliculitis ( Pityrosporum folliculitis [P. folliculitis]) and acneiform eruption, based on clinicopathological features, is challenging for clinicians. In the literature, the histopathological differences between P. folliculitis and acneiform eruption lesions have been poorly described. We aimed to determine the clinicopathologic distinctions between P. folliculitis and acneiform eruption by retrospectively analyzing the histology of hematoxylin and eosin stained tissue sections obtained from 52 patients diagnosed with these lesions. The presence of fungal spores in the follicular lumen was most consistent with a P. folliculitis diagnosis ( P  < 0.001). However, intrafollicular inflammation ( P  = 0.009), irregular patterns of keratin plugging ( P  = 0.008), and nuclear dust in the follicular lumen ( P  < 0.001) favored an acneiform eruption diagnosis. These intrafollicular characteristics and inflammatory differences are believed to be caused by necrotic keratinocytes that lead to vacuolar changes in the follicular wall ( P  = 0.013). We did not observe any difference between P. folliculitis and acneiform eruption lesions in terms of perifollicular inflammatory cell infiltration. Our study demonstrated that significant differences exist between P. folliculitis and acneiform eruption lesions relative to the presence of necrotic keratinocytes in the follicular wall, intrafollicular characteristics, and inflammatory cell infiltrations. Necrotic keratinocytes are believed to have a key role in these differences. These findings may contribute to an improved understanding of the pathogenesis and differential diagnosis of P. folliculitis and acneiform eruption.